The ‘Proverbia Grecorum’ - Simpson, Dean (Traditio, 1987)
Statements in Latin concerning such topics as wisdom, truth, and virtue, attributed to the Proverbia Grecorum (less often the Parabolae Gregorum), are found in a number of early medieval manuscripts. They are of interest because of their stated connection with the Greeks, which pertains to the knowledge of Greek and Greek learning in the early medieval West, and because of the obscure vocabulary many of the proverbs contain, which relates to the study of the latinity of early medieval, especially insular, scholars. New findings concerning the origin and transmission of these statements have increased their importance because they have revealed connections between them and other important early medieval Latin texts, notably the Collectio canonum Hibernensis and certain florilegia found in the miscellaneous Collectaneum of Sedulius Scottus. The Proverbia Grecorum have been edited and studied in detail only once, by Sigmund Hellmann, in 1906. Since then new statements attributed to the Proverbia Grecorum have been found, and the characterization of early medieval Latin culture has been significantly revised. Hellmann's text, furthermore, has been found to be faulty in a number of places. Therefore, there is a need for a full re-edition and study of this proverb collection. This has been undertaken in the present work. Following this essay, which defines the current state of knowledge of the Proverbia Grecorum, there is a critical edition of all statements identified as Proverbia Grecorum. This is followed by a commentary in which parallel texts are cited, and points of linguistic interest are noted.